2017
DOI: 10.3892/mmr.2017.6921
|View full text |Cite
|
Sign up to set email alerts
|

Human decidua mesenchymal stem cells regulate decidual natural killer cell function via interactions between collagen and leukocyte-associated immunoglobulin-like receptor 1

Abstract: The development of maternal tolerance to the fetal allograft in critical for the maintenance of the pregnancy, and it is accompanied by the development of a special decidual natural killer (dNK) cell tolerance phenotype. To understand the factors that influence dNK cells during early pregnancy, the present study aimed to identify mesenchymal stem cells (MSCs) from human first‑trimester deciduas, termed decidual MSCs (DMSCs), and to investigate the effect of DMSCs on the regulation of dNK cells via collagen. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…The different results, which may be because of the different origin and culture conditions of MSCs, remain to be further studied. MSCs exert regulatory effects on various cells of the immune system, such as dendritic cells, NK cells, and T cells (41,42). Results from numerous studies and our laboratory showed that hPMSCs can induce the generation of different Treg subsets, such as CD4 + CXCR5 + Foxp3 + , CD4 + CD25 + Foxp3 + , CD8 + CD25 + Foxp3 + , CD4 + IL-10 + , and CD8 + IL-10 + Treg subsets (18).…”
Section: Discussionmentioning
confidence: 98%
“…The different results, which may be because of the different origin and culture conditions of MSCs, remain to be further studied. MSCs exert regulatory effects on various cells of the immune system, such as dendritic cells, NK cells, and T cells (41,42). Results from numerous studies and our laboratory showed that hPMSCs can induce the generation of different Treg subsets, such as CD4 + CXCR5 + Foxp3 + , CD4 + CD25 + Foxp3 + , CD8 + CD25 + Foxp3 + , CD4 + IL-10 + , and CD8 + IL-10 + Treg subsets (18).…”
Section: Discussionmentioning
confidence: 98%
“…This may potentiate the transition of peripheral into decidual NK cells, a process critical for adequate decidual function. Decidual MSCs in addition regulate dNK through their intracellular cytokine expression profile, including TNF-α and IL-4 and via the interaction between collagen and LAIR-1 ( 171 ). Bone marrow-derived MSCs are also capable of modulating NK cells by inhibiting their proliferation, cytokine secretion, and cytotoxicity against HLA-class I- expressing targets, either via soluble factors or via cell-to-cell specific interactions ( 172 , 173 ).…”
Section: Msc Regulation Of Innate Immune System Response Is Impaired mentioning
confidence: 99%
“…Both autologous and allogeneic MSCs have been found dissolved by cytokineactivated NK cells when sufficient activating receptors expressing on NK cells [98]. Incubation of MSCs with IFN-γ partially protected them from NK-cell-mediated cytotoxicity, suggesting a microenvironment rich in IFN-γ might favor MSCs inhibiting NK cells, whereas in the absence of IFN-γ, the balance would be tilted towards NK cells eliminating MSCs [92][93][94][95][96][98][99][100]. Similarly, it has been shown that TLR4-primed MSCs were more resistant than unprimed MSCs to activated NK cell killing, and in contrast, no comparable protection was observed after TLR7/ 8-priming of MSCs [97,[101][102][103].…”
Section: Effect Of Mscs On Natural Killer (Nk) Cellsmentioning
confidence: 99%
“…MSCs can be strong inhibitors of NK cells in terms of proliferation and cytotoxicity. It has been shown the presence of MSCs substantially reduced IL-2/15-induced NK cell proliferation, cytotoxicity, the production of IFN-γ, and the level of perforin and granzymes [ 93 95 ]. Furthermore, the expression of surface receptors, such as NKp30, NKp44, and natural-killer group 2 member D (NKG2D) typically involved in NK cell activation and target cell killing, were also downregulated.…”
Section: Msc Therapy: Biological Properties Supporting Clinical Usementioning
confidence: 99%